Ուշ միջնադարի մի նորահայտ զրույց - Քեշիշյան, Վարդի («Նաիրի» հրատ.)
The ―Tales of Carthage‖ by Hovhannes of Beraia, a famous ballad maker of Late Middle Ages, is still unknown for wide circle of specialists and naturally has dropped out of scientific circulation. Only the bibliographic lists and catalogues of manuscripts of the Matenadaran provide information about the existence of this work.
Keywords: Հայ միջնադարյան գրականություն